2006
DOI: 10.1121/1.2216899
|View full text |Cite
|
Sign up to set email alerts
|

Radiation forces exerted on arbitrarily located sphere by acoustic tweezer

Abstract: In a previous paper acoustic radiation force on a lipid sphere in a 100-MHz focused Gaussian field was calculated to demonstrate the acoustic tweezer effect near the focus. The theoretical formulation was based on the situation where the sphere is centered along the beam axis. Given intensity distribution independent of the x axis, it was then approximated by a cylindrical model for the sake of simplicity. Only the axial forces were considered because no lateral forces exist due to an object's symmetry. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 12 publications
3
52
0
Order By: Relevance
“…These studies have shown that Gaussian beams can be used for trapping particles in both axial and transverse directions, although the latter is expectedly much easier. These theoretical findings were also experimentally confirmed using a single focused Gaussian ultrasound beam, for entrapment of very fine lipid droplets (in order of 125 m) [41][42][43]. Besides the transverse entrapment, it was also shown that a high frequency focused beam could be used to laterally move micro-droplets towards the focus point.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…These studies have shown that Gaussian beams can be used for trapping particles in both axial and transverse directions, although the latter is expectedly much easier. These theoretical findings were also experimentally confirmed using a single focused Gaussian ultrasound beam, for entrapment of very fine lipid droplets (in order of 125 m) [41][42][43]. Besides the transverse entrapment, it was also shown that a high frequency focused beam could be used to laterally move micro-droplets towards the focus point.…”
Section: Introductionsupporting
confidence: 51%
“…The above observations suggest that negative axial and lateral radiation forces can be produced generally when a focused Gaussian beam is concentrated on the very top (or bottom) of the particle. To complete the discussion, it is worth mentioning that the problem of lateral movement of spherical particles using Gaussian beams, to pull them towards the beam axis has been previously reported by other authors [41][42][43]. The magnitude of such attractive transverse forces is understandably greater than the negative axial forces, as seen in Figs.…”
Section: Numerical Results and Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Initially, these 'acoustical tweezers' used opposing focused transducers to produce a trap at their, common, focal point (Wu 1991). More recent theoretical (Lee et al 2005;Lee & Shung 2006) and experimental (Lee et al 2009) work has demonstrated the feasibility of using a single focused transducer working at a high frequency (30 MHz) to trap particles much larger than a wavelength in diameter against a surface. Particle manipulation has been achieved by moving the transducer and hence the focal position.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The manipulation of spheres, drops, bubbles, and other objects using radiation force has also been explored. [11][12][13][14][15][16] Methods based on radiation force have been developed to characterize different materials such as soft gelatin phantoms and soft tissue. [17][18][19] One of the emerging uses of ultrasound radiation force is its use in ultrasound-based elasticity imaging.…”
Section: Introductionmentioning
confidence: 99%